Pengaruh Pemberian Jus Averrhoa carambola terhadap Penurunan Tekanan Darah pada Lansia Penderita Hipertensi - Putri Aulia Arza; Andri Irawan (Politeknik Kesehatan Tanjung Karang, 2018)
Hypertension, or high blood pressure, is a very common and serious condition that can lead to or complicate many health problems.Solving this problem by nonpharmacologic, it is needed to bedeveloped, for example with consuming star fruit juice. Star fruit (AverrhoaCarambola) is rich in Vitamin C, and contains high levels of potassium and low in sodium which has the effect of lowering blood pressure. This study aimed to determine the effect of star fruit juice to the reduction of blood pressure in elderly hypertensive patients. The study used a pre-experimental study with one group pretest-posttest design with 10 respondents selected by purposive sampling. The results showed that systolic blood pressure in statistical analysis showed that p=0.000 (p˂ 0.05) means that Hypotheses received or systolic blood pressure between before and after consumption star fruit juice significantly their influence. That the diastolic blood pressure in statistical analysis showed that p=0.001 (p˂0.05), which means that Hypotheses received or systolic blood pressure between before and after consumption star fruit juice significantly their influence.The result is expected to give any benefit for the society and become one of the solutions to treat the hypertension suffers.